1993
DOI: 10.1046/j.1365-313x.1993.04030411.x
|View full text |Cite
|
Sign up to set email alerts
|

Myb genes from Hordeum vulgare: tissue‐specific expression of chimeric Myb promoter/Gus genes in transgenic tobacco

Abstract: The structures of the three Myb-related genes Hv1, Hv5 and Hv33 from barley were determined. They contain a single intron located in the second repeat unit of the Myb-related domain. By analogy to the animal MYB oncoproteins this conserved region of the gene product was shown by filter-binding experiments to exhibit nucleic acid-binding activity. Tobacco plants transgenic for chimeric Myb promoter/Gus genes express the enzyme in a developmentally controlled and tissue-specific manner. During germination and ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

1995
1995
1996
1996

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…Sequence comparisons between R2 and R3 regions from other plant and animal Myb proteins show that the GAMyb is most closely related to MYB.Ph3 (86% identity), which is expressed in petunia flowers (Avila et al, 1993). There is less sequence identity between the R2 and R3 repeats of GAMyb and the other barley Myb proteins, HV1, HV5, and HV33 (54 to 63%) (Marocco et al, 1989;Wissenbach et al, 1993). Outside of the putative DNA binding domain, and nine amino acids immediately C terminus of the R3 region (146 to 154), there is a stretch of 15 amino acids in the C-terminal position of the GAMyb open reading frame (374 to 388) that shares 73% identity with amino acids 329 to 343 of MYB.Ph3.…”
Section: Cloning Of Gamyb Cdna and Sequence Comparison With Myb-relatmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequence comparisons between R2 and R3 regions from other plant and animal Myb proteins show that the GAMyb is most closely related to MYB.Ph3 (86% identity), which is expressed in petunia flowers (Avila et al, 1993). There is less sequence identity between the R2 and R3 repeats of GAMyb and the other barley Myb proteins, HV1, HV5, and HV33 (54 to 63%) (Marocco et al, 1989;Wissenbach et al, 1993). Outside of the putative DNA binding domain, and nine amino acids immediately C terminus of the R3 region (146 to 154), there is a stretch of 15 amino acids in the C-terminal position of the GAMyb open reading frame (374 to 388) that shares 73% identity with amino acids 329 to 343 of MYB.Ph3.…”
Section: Cloning Of Gamyb Cdna and Sequence Comparison With Myb-relatmentioning
confidence: 99%
“…The time COUrSe in Figure 56 shows that the increase in expression of the The two ammo acid repeats, R2 and R3 of GAMyb, are compared with the repeats of other barley Myb homologs, Hv1, Hv5, and Hv33 (Marocco et al, 1989;Wissenbach et al, 1993), petunia Myb homolog, PHMYB3 (Avila et al, 1993), maize Myb homolog, ZmC1 (Paz-Ares et al, 1987), and human c-Myb (Majello et al, 1986). Shaded boxes indicate the amino acids that are identical to those of GAMyb.…”
Section: Gamyb Gene Expression 1s Regulated By Gamentioning
confidence: 99%
“…The dendrogram based on amino acid similarity within the DNA-binding repeats (Fig. 3) indicates that this region of THM27 is most similar to those of two barley (Hvl and Hv5 [47]) and two Antirrhinum (AM308 and AM330 [17]) Myb proteins. Interestingly, outside this conserved region THM27 has two more motifs, GIDPTTH and CLPDLN-LELRISPP, which are also present in the same four Myb proteins (with the exception of the latter motif in AM330).…”
Section: Discussionmentioning
confidence: 99%
“…3) indicates that THM1 and THM27 are more similar to Myb-related proteins from other plant species than they are to one another. The DNA-binding domains of THM 1 and THM27 exhibit only 64 ~o similarity, whereas those regions of THM27 and AM308 from antirrhinum [17] are 96~0 similar, and the value for THM1 and Hv33 from barley [47] is 72~o. Outside the DNA-binding domain, no extensive amino acid similarity is evident between the proteins encoded by THM1 and THM27.…”
Section: T T a T T C T T T A A T T C A C C A A T • A G T A T C A G mentioning
confidence: 99%
“…Experimental evidence includes the demonstration that plant Myb proteins interact specifically with AC elements in vitro, as well as activating transcription via AC elements in a protoplast transient-expression system and in yeast ( [ 12,4], Yung and Lin, personal communication). In several plants species, Myb proteins are encoded by an number of differentially expressed genes [7,1,17]. Furthermore, it has been demonstrated that different Myb proteins have different affinities for different Myb-binding sites [ 15 ].…”
mentioning
confidence: 99%